2014
DOI: 10.1007/s11156-014-0485-x
|View full text |Cite
|
Sign up to set email alerts
|

Dual-class versus single-class firms: information asymmetry

Abstract: I examine information asymmetry in dual-class firms in general and when they need (do not need) additional external capital. In general the results show that dual-class firms have higher information asymmetry than single-class firms. When dual-class firms need additional external financing, the gap in information asymmetry between dual-class firms and single class firms is narrower. I find that as the need of additional external capital increases, the difference in information asymmetry between dual-class and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…warrington.ufl.edu/ritter/ipo-data/. 15 Following prior literature (e.g., Gompers et al, 2010;Lim, 2016;Nguyen To identify firms that converted to a dual-class share structure through recapitalization, we search the CRSP files for issues with identical six-digit CUSIPs but different two-digit extensions to find firms with multiple classes of shares from 2002 through 2012.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…warrington.ufl.edu/ritter/ipo-data/. 15 Following prior literature (e.g., Gompers et al, 2010;Lim, 2016;Nguyen To identify firms that converted to a dual-class share structure through recapitalization, we search the CRSP files for issues with identical six-digit CUSIPs but different two-digit extensions to find firms with multiple classes of shares from 2002 through 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrated managerial ownership is associated with low credibility of accounting information (DeAngelo & DeAngelo, 1985;Francis et al, 2005), while the segregation between cash flow rights and voting rights is associated with severe conflicts of interest between the controlling insiders and the inferior class shareholders (Masulis et al, 2009). As a result, dual-class firms are often associated with poor information environment (e.g., Forst, Hettler, & Barniv, 2019;Lim, 2016), low informativeness of earnings (Francis et al, 2005), and are often perceived as having "bad governance" (Gompers et al, 2010). As a result, dual-class firms are often associated with poor information environment (e.g., Forst, Hettler, & Barniv, 2019;Lim, 2016), low informativeness of earnings (Francis et al, 2005), and are often perceived as having "bad governance" (Gompers et al, 2010).…”
Section: Prior Research and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…). It has also been shown that DC firms have more acute informational asymmetries than SC firms (see Lim ; and Li et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Because cashflow and voting rights are separated under such a mechanism (in contrast to a one-share-one-vote system), controlling shareholders can expropriate wealth from the firm for their own benefit at very low personal cost (see DeAngelo and DeAngelo 1985;Grossman and Hart 1988; and more recently, Masulis et al 2009). It has also been shown that DC firms have more acute informational asymmetries than SC firms (see Lim 2010;. Such agency and informational costs can impose greater financing constraints on DC firms and results in higher costs of capital as investors often demand a larger premium to hold their stock (see Claessens et al 2002;Lins 2003;Durnev and Kim 2005).…”
mentioning
confidence: 99%